Rates and Predictors of Consistent Condom-use by People Living with HIV/AIDS on Antiretroviral Treatment in Uganda - Ayiga, Natal (Journal of Health, Population and Nutrition, 2012)
Antiretroviral treatment (ART) has been recognized as one of the methods for reducing the risk of HIV transmission, and access to this is being rapidly expanded. However, in a generalized HIV epidemic, ART could increase unprotected sex by people living with HIV/AIDS (PHAs). This paper assessed the rates and predictors of consistent condom-use by sexually-active PHAs after initiating ART. The study used crosssectional data on sexual behaviour of 269 sexually-active ART-experienced individuals (95 males and 174 females) aged 18 years and above. The results revealed that 65% (70% of men and 61% of women) used condom consistently after initiating ART. Consistent use of condom was more likely if PHAs had secondary- or tertiary-level education and had more than one sex partner in the 12 months preceding the study.However, PHAs were less likely to have used condom consistently if they worked in the informal and formal sectors, belonged to the medium- and high-income groups, and were married. PHAs, who were on ART for less than 1 year and 1-2 year(s), had a good self-perception of health, had a sexual partner who was HIV-negative or a partner with unknown HIV status, and desired to bear children, were also less likely to have used condom consistently. The paper concluded that, although the majority of PHAs consistently used condom, there was potential for unprotected sex by PHAs on ART. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12290 J HEALTH POPUL NUTR 2012 Sep;30(3):270-280